Lost in Translation? The Prevalence of Foreign Drink Names in Arabic Coffee Menus - Mohammed, Abdullah Saleh Aziz (International Journal of Language and Literary Studies, 2025)
This study aims to explore coffee drinks branding strategies in the Arab world, with a particular reference to the Saudi context. The study uses a mixed-methods approach consisting of a) 30 menus of local coffee shops; b) 31 responses to a questionnaire for coffee shop owners/managers; c) 133 responses to a customer perceptions questionnaire; d) 5 guided interviews with coffee shop owners/managers. The naming strategies discussed are transliteration, translation and localisation. The results show heavy inclination towards transliteration, reflecting a tendency to globalisation and the influence of international branding strategies. The use of translation is limited to menu items that can have resonance with local culture and local customer perceptions. Localisation is often used to echo tenacity to local culture and also as a strategy to bridge the gap between local heritage and global market influx. The study's value hinges on revealing the tension of naming products between globalised imports and local sentiments, with signals favouring openness to the global market tendencies.